Dispute settlement in international space law : a multi-door courthouse for outer space - Goh, Gérardine Meishan (Studies in space law, 2007)
Drawing on lessons learned in international law, juridical dispute settlement, entrepeneural efficiency, science and technology and space policy, this book offers a comprehensive insight into dispute settlement and proposes a workable and enforceable framework for dispute settlement concerning space activities.